Decreased Cognitive Function in People with Type 2 Diabetes Mellitus - Shinta Kaozar Wiratman; Widya Hary Cahyati (Universitas Muhammadiyah Semarang, 2021)
ABSTRACTBackground: The number of cases and the prevalence of diabetes has continued to increase over the past few decades. DM itself is associated with an increased risk of cancer, kidney failure, stroke, and decreased cognitive function that leads to dementia. In 2016 Indonesia has an estimated 1.2 million people with dementia and is expected to grow to 4 million by 2050.Objective: The purpose of this study was to find out the risk factors for decreased cognitive function in people with type 2 diabetes mellitus.Method: This type of research is observational analytics with cross sectional design. The sample was 62 respondents with purposive sampling techniques. The instrument used in the study was a structured questionnaire. Measurement of cognitive function using MoCA-INA questionnaire. Data collection is done by interview method to respondents.Result: The results showed that there was a relationship between the age of the respondent (PR= 2.98; 95% CI= 0.97-9.17), and the respondent's blood sugar level (PR= 3.31; 95% CI= 1.12-9.74) to decreased cognitive function in people with type 2 diabetes mellitus.Conclusion: Age and blood sugar levels of respondents contributed to decreased cognitive function of people with type 2 diabetes mellitus.